Recent Advances in Two-Dimensional Materials with Charge Density Waves: Synthesis, Characterization and Applications - Mongur Hossain; Zhaoyang Zhao; Wen Wen; Xinsheng Wang; Juanxia Wu; Liming Xie (Crystals, 2017)
Recently, two-dimensional (2D) charge density wave (CDW) materials have attracted extensive interest due to potential applications as high performance functional nanomaterials. As other 2D materials, 2D CDW materials are layered materials with strong in-plane bonding and weak out-of-plane interactions enabling exfoliation into layers of single unit cell thickness. Although bulk CDW materials have been studied for decades, recent developments in nanoscale characterization and device fabrication have opened up new opportunities allowing applications such as oscillators, electrodes in supercapacitors, energy storage and conversion, sensors and spinelectronic devices. In this review, we first outline the synthesis techniques of 2D CDW materials including mechanical exfoliation, liquid exfoliation, chemical vapor transport (CVT), chemical vapor deposition (CVD), molecular beam epitaxy (MBE) and electrochemical exfoliation. Then, the characterization procedure of the 2D CDW materials such as temperature-dependent Raman spectroscopy, temperature-dependent resistivity, magnetic susceptibility and scanning tunneling microscopy (STM) are reviewed. Finally, applications of 2D CDW materials are reviewed.